Strukturalisasi kurikulum pendidikan dalam Hadits sebagai landasan kurikulum pendidikan modern - Nuryanti, Nuryanti; Husti, Ilyas; Nurhadi, Nurhadi (Program Studi Pendidikan Agama Islam STAI Auliaurrasyidin Tembilahan, 2024)
The hadiths of Prophet Muhammad SAW, as one of the primary sources of Islamic teachings, hold significant potential as a foundation for curriculum development in education. However, their utilization in curricula remains limited, with the integration of their values often lacking systematic structure. This study aims to analyze the application of hadith structuralization in the development of modern educational curricula. The research employs a qualitative method with a case study approach, using in-depth interviews, observations, and document analysis from several Islamic educational institutions implementing hadith-based curricula. The findings reveal that the structuralization of hadiths provides a solid foundation for balanced education, integrating academic achievement with moral character development. Hadithsresponsibilitiesnsultation, and social responsibility are relevant in designing curricula that are adaptive to globalization while remaining rooted in Islamic values. Thus, hadiths serve as a cornerstone for curricula that produce knowledgeable and virtuous individuals.